The effects of lifestyle, dietary dairy intake and diabetes on bone density and vertebral deformity prevalence: the EVOS study. - Lunt, M; Masaryk, P; Scheidt-Nave, C; Nijs, J; Poor, G; Pols, H; Falch, J; Hammermeister, G; Reid, D; Benevolenskaya, L; Weber, K; Cannata, J; et al. (2001)
The risk of low and moderate energy fracture is related to bone mineral density (BMD). Yet it is uncertain whether the epidemiologic determinants of fracture risk are the same as for low bone density. The European Vertebral Osteoporosis Study was a population-based prevalence study of vertebral deformity in 36 age-stratified population samples aged 50-80 years. In nearly 4000 subjects (13 centers), BMD measurements were also made at the spine, femoral neck and femoral trochanter. To investigate whether effects of reported physical activity on spine deformity risk were mediated through BMD, we modeled these and other risk factor data with BMD as the dependent variate after adjusting for age, center, sex and body mass index (BMI). The significant determinants of vertebral deformity risk were also entered into logistic models of deformity risk that included BMD measurements as covariates. Both current and lifetime physical activity were positively associated with BMD. This effect was stronger with hip BMD than with spine BMD. Lifetime smoking exposure was associated with reduced BMD. Type 2 diabetes mellitus was associated with increased BMD. Weak positive associations were found between consumption of dairy products and BMD at the three measured sites and these were strengthened by an interaction with measures of physical activity in men. Physical activity in women had the largest beneficial effect in lean women and in women exposed to hormone replacement therapy. When fracture risk was modeled with BMD as a covariate, the lifestyle and dietary determinants became less strongly related to vertebral deformity risk, suggesting that BMD may have acted as an intermediary variable. However, heavy physical activity in men still increased spine deformity risk after adjusting for BMD. It is concluded that physical activity in both genders and milk consumption in young women might protect against vertebral deformities in later life through their effects on bone density. The adverse effect of smoking on BMD was confirmed. Heavy physical activity in men might increase spine deformity risk even when BMD is normal.